2016
DOI: 10.11138/jts/2016.4.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in total knee arthroplasty: efficacy of a multimodal opiate-free protocol

Abstract: Purpose: this study was conducted to identify the most effective method of postoperative pain management, comparing the intravenous opiate infusion protocol with the use of a single periarticular local anesthetic infiltration (LAi) in patients undergoing total knee arthroplasty (tKA) surgery. Methods: 50 patients submitted to tKA surgery between 2013 and 2015 were divided into two groups. Buprenorphine was administered intravenously to the patients in Group A, while the Group B patients received a single peria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the subsequent 24 hours, the patients who underwent rTKA only used 1.33 times more opioids than the pTKA group. Thus, the multimodal pain protocols that have been effective for patients who underwent pTKA [7][8][9] do not appear to be as effective for our patients who underwent rTKA. By the second day, the differences in opioid requirements are less pronounced, suggesting that the opportunity for improved pain control is in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the subsequent 24 hours, the patients who underwent rTKA only used 1.33 times more opioids than the pTKA group. Thus, the multimodal pain protocols that have been effective for patients who underwent pTKA [7][8][9] do not appear to be as effective for our patients who underwent rTKA. By the second day, the differences in opioid requirements are less pronounced, suggesting that the opportunity for improved pain control is in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 83%
“…With the focus on opioid use, a considerable amount of attention has gone into deriving new opioid-sparing or reduced opioid pain management programs to follow total joint arthroplasty. These opioid-sparing protocols have become very effective at reducing narcotic consumption and improving function after primary total knee arthroplasty (pTKA), including at our own institution [7][8][9][10][11]. But while multiple studies have described pain management plans to reduce opioid consumption after pTKA, there has been minimal investigation into whether the consumption of opioids after revision TKA (rTKA) is comparable with pTKA and whether these multimodal pain plans are able to be translated to rTKA in the acute postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the current attention to the opioid epidemic, there has been more and more focus on opioid sparing protocols for primary joint arthroplasty but this has not yet been assessed as to how these protocols apply to revision joint arthroplasty. [18][19][20][21][22][23][24][25] As it has been shown that optimal pain control following THA is necessary for reduction of postoperative complications, to improve patient satisfaction, and to expedite patient recovery and discharge it is important that we understand that pain protocols for revision THA patients clearly need different considerations than those for primary THA in order to facilitate patient recovery. 19 There were several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of arthroplasty is immediate resumption of full weight-bearing and ambulation (as in hip fracture management) to prevent thrombo-embolic and decubitus-related complications. 16 , 28 …”
Section: Treatmentmentioning
confidence: 99%